2020
DOI: 10.1007/s11136-020-02539-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences of an electronic PRO tailored feedback system for symptom management following upper gastrointestinal cancer surgery

Abstract: Purpose Complications following upper gastrointestinal (UGI) surgery are common. Symptom-monitoring following discharge is not standardized. An electronic patient-reported outcome (ePRO) system providing feedback to patients and clinicians could support patients and improve outcomes. Little is known about patients' experiences of using such systems. This qualitative sub-study explored patients' perspectives of the benefits of using a novel ePRO system, developed as part of the mixed methods eRAPID pilot study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Several studies (3/61, 5%) exploring patients’ perceptions about ePROM systems found that patients agreed that it was easy to remember their symptoms when required to recall them at clinic encounters [ 50 , 54 - 56 ]. The following observations by Lee et al [ 57 ] and Richards et al [ 58 ] provide insights into how more frequent self-reporting might help patients:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (3/61, 5%) exploring patients’ perceptions about ePROM systems found that patients agreed that it was easy to remember their symptoms when required to recall them at clinic encounters [ 50 , 54 - 56 ]. The following observations by Lee et al [ 57 ] and Richards et al [ 58 ] provide insights into how more frequent self-reporting might help patients:…”
Section: Resultsmentioning
confidence: 99%
“…And then the reality of how I really am and then slowly seeing the recovery over that time has been very helpful. [ 58 ]…”
Section: Resultsmentioning
confidence: 99%
“…A mixed-methods feasibility pilot study of the eRAPID surgery system was developed between August 2017 and March 2018. Two publications reporting the findings have been published; 136,137 see Appendix 1, eRAPID radiotherapy developmental paper.…”
Section: Feasibility Pilot Studymentioning
confidence: 99%
“…Patients reported feeling empowered to take a central role in their own recovery because the system provided new and tailored symptom self-management advice and reminded them of and reinforced the guidance that they had previously received. Patients also stated that the system enabled them to overcome feelings of isolation and uncertainty post discharge 136 (see Appendix 1, eRAPID radiotherapy developmental paper).…”
Section: Qualitative Interviews With Patients and Health-care Profess...mentioning
confidence: 99%
“…Samuel et al [35] investigate the question of how far the adoption of health information technologies varies along social gradients and describe differences associated with ethnicity in bladder and prostate cancer patients. The two main themes identified in the second paper [36] offer additional insight into the potential of electronic PRO (ePRO) systems when supporting post-hospital or outpatient care: the system was described as providing "reassurance" and "empowerment" (Table 3 in [36]), pointing to a range of functions such a system could fulfill in such a setting. A report investigating the implementation of a monthly text-based symptommonitoring program found such a system feasible, with good adherence rates, and was positively perceived by patients and staff [37].…”
Section: The Special Issuementioning
confidence: 99%